(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Violence against women is a practice that persists in all societies across the globe. The range of actions and omissions that amount to violence has evolved over time, to recognise harmful practices that do not necessarily result in physical harm. Such actions or omissions include economic and psychological forms of violence. The evolving definition of violence is reflected in many global and regional human rights instruments. However, the approach to such recognition and measures proposed to address economic and psychological forms of violence vary considerably from one instrument to another. This article assesses the extent to which economic and psychological forms of violence are addressed in the norms and standards of the African Union. A systematic review of the applicable instruments and the jurisprudence of key human rights bodies reveals that the recognition of economic and psychological forms of violence rarely goes beyond the definition clause of the respective instruments. As a result, jurisprudential engagement on, and the framing of measures for response to these forms of violence is limited. The failure to adopt a consistent, robust and purposive approach to violence, which articulates measures necessary to address all the forms of violence, undercuts the protection available to women who suffer from economic and psychological forms of violence. This article makes the case that consistent recognition and specific articulation of economic and psychological forms of violence as distinct types of violence, as in the approach of the Istanbul Treaty, is necessary to fulfil the promise of protection from ‘all forms of violence’. Such express recognition in multilateral instruments is important to influence domestic law to follow suit.